Ni(ii)-catalyzed asymmetric addition of arylboronic acids to cyclic imines. Issue 3 (16th December 2016) - Quan, Mao; Tang, Liang; Shen, Jiaqi; Yang, Guoqiang; Zhang, Wanbin
Abstract : A Ni(ii )-catalyzed asymmetric addition of arylboronic acids to cyclic imines has been realized using a tropos biphenyl phosphine-oxazoline ligand. Abstract : A Ni(ii )-catalyzed asymmetric addition of arylboronic acids to cyclic aldimines and ketimines is reported. Our tropos phosphine-oxazoline biphenyl ligand is crucial for the high catalytic activity, which coordinates to Ni(ii ) to form a complex with a single axial configuration. The desired chiral amine products could be prepared with excellent yields (up to 99%) and enantioselectivities (up to 99.8%) under mild reaction conditions.